The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/pon.3188
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of desire for help in oncology outpatients reporting pain or distress

Abstract: Although desire for help with pain and distress increased with respective symptom intensity, many patients indicated they did not want help with these symptoms. Patient reluctance to seek help may constitute a barrier to realising the full potential of screening programs in reducing pain and distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 38 publications
(83 reference statements)
3
29
1
2
Order By: Relevance
“…Because in clinical (non‐research) settings, a patient is referred to definite treatment, the weighted uptake rate of 50.01% for those offered a definite treatment is more likely to be representative of typical clinical care. Even this weighted uptake rate is higher than seen in surveys, which report that between 14 and 41% of cancer patients show a definite interest in psychological support possibly suggesting that the higher uptake rates in the present study are inflated by an altruistic desire to participate in the research. Further, uptake was lower in groups that were selected for higher distress.…”
Section: Discussioncontrasting
confidence: 84%
“…Because in clinical (non‐research) settings, a patient is referred to definite treatment, the weighted uptake rate of 50.01% for those offered a definite treatment is more likely to be representative of typical clinical care. Even this weighted uptake rate is higher than seen in surveys, which report that between 14 and 41% of cancer patients show a definite interest in psychological support possibly suggesting that the higher uptake rates in the present study are inflated by an altruistic desire to participate in the research. Further, uptake was lower in groups that were selected for higher distress.…”
Section: Discussioncontrasting
confidence: 84%
“…It is encouraging that people did not indicate a nihilistic attitude to help for distress, in that few said they ‘didn't think anything could help’. Although stigma is a known barrier in seeking mental health services more generally, it appears to be less influential in cancer . However, we note that the item representing stigma in this study may not adequately capture this concept and that stigma may be subsumed in the desire to self‐manage.…”
Section: Discussionmentioning
confidence: 73%
“…The relationship between receiving help and younger age and female gender is consistent with previous work. We have previously summarised findings regarding gender differences in desire for help with distress among oncology patients . We found about half the studies reported an association which consistently indicated higher desire for help among women.…”
Section: Discussionmentioning
confidence: 99%
“…Clover et al. found that number to be as high as 71 % . Recently, a similarly high percentage of patients who declined such a program was reported for both outpatients and inpatients at a German SCC .…”
Section: Discussionmentioning
confidence: 93%